Extracorporeal shockwave therapy in an immobilized knee model in rats prevents progression of joint contracture. Issue 5 (7th September 2022) - Iwatsu, Jun; Yabe, Yutaka; Kanazawa, Kenji; Itaya, Nobuyuki; Sogi, Yasuhito; Saijo, Yoshifumi; Aizawa, Toshimi; Hagiwara, Yoshihiro
Abstract: Joint immobilization, which ensures rest and accelerates tissue recovery in musculoskeletal disorders, often causes joint contracture, for which there is still no effective prevention. To address this, we investigated the effects of extracorporeal shockwave therapy (ESWT) in preventing joint contracture, in a unilaterally immobilized knee rat model. Under general anesthesia, ESWT (0.25 mJ/mm 2, 3000 shot, 4 Hz, 3 days/week) was administered from 1 day after immobilization up to 2, 4, and 6 weeks. The immobilized control group received general anesthesia without ESWT. We evaluated joint angle, tissue elasticity, and gene and protein expression related to fibrosis, inflammation, and angiogenesis in the joint capsule. Relative to the control, the ESWT group had greater joint angle at 4 and 6 weeks, and lower posterior‐capsule elasticity at 6 weeks. In the ESWT group, at 6 weeks, gene expression of collagen type I ( col1α1 ), connective tissue growth factor ( CTGF ), and α‐smooth muscle actin ( α‐SMA ) was significantly downregulated, whereas interleukin‐6 ( IL‐6 ) and hypoxia‐inducible factor‐1α ( HIF‐1α ) gene expression was upregulated, relative to that in the control. Compared with that in the control, at 4 and 6 weeks, the ratio of CTGF + cells was significantly lower in the ESWT group; at 4 weeks, the ESWT group had significantly fewer CD68 + cells in the adhesion area, and at 6 weeks, significantly more blood vessels. Statement of Clinical Significance: In a rat model, ESWT counteracted fibrosis, suppressed macrophage infiltration, and promoted neovascularization, reducing elasticity, and increasing joint range‐ofmotion. ESWT offers a potential new strategy to prevent progression in joint contracture.